Исследование гидросистемы на окраине античного городища Тасуново (Кош-Кую) - Винокуров, Н.И.; Павловский, А.И. (Боспорские исследования, 2009)
Topographic GPS work has been done at the area of the city-site Tasunovo; a topographic plan of the city site has been made completely. More than 200 meters of an underground drained system has been examined on the north and west periphery of the city site. Archaeological digs show the system was functioning with significant reconstructions from the first centuries AD till the 70s of the 20th century. Constructive elements of the hydro system have been singled out in the process of research of the eminence foot where the ancient city site Tasunovo is situated.